(untitled) (World Science, 2018)
The perspective of urban fabric transformation is formulated in connection with the reduction of the influence of industrial factors and the development of a highly informatized society. A key element of the practical implementation of the impulse development strategy of the city in the 21st century is the prediction of the development of a basic urban unit of a post-industrial city, which in this work is called the local cluster. The phenomenon of impulse development of urban fabric is analyzed, the system of laws and principles that transform urban complexes into post-industrial ones is outlined. It has been found that the impulse strategy, in modern conditions, should be made of two components and contain both city-wide and local levels of management and modeling. The level of local clusters, that is being discussed, involves the presence of a combination of impulse factors, the content and names of which are presented in this work.